Prevalence of vancomycin-resistant enterococci among children with end-stage renal failure - Baum, Heike von; Schehl, Joachim; Geiss, Heinrich K.; Schaefer, Franz (Clinical infectious diseases, 1999)
To evaluate the prevalence of colonization with vancomycin-resistant enterococcus (VRE) in end-stage renal failure (ESRF), we screened the intestinal flora from 338 pediatric ESRF patients treated in 13 pediatric nephrology units in mid-Europe. Eighty-one patients were undergoing hemodialysis, 66 were undergoing chronic peritoneal dialysis, and 191 were transplant recipients. A total of 363 enterococcal strains were recovered from 232 patients. Twenty-seven enterococcal strains from 24 patients (7.1%) had reduced susceptibility to vancomycin (minimal inhibitory concentration [MIC], >4 μg/mL). Although two patients (0.6%) carried enterococci with high-level resistance to vancomycin (MIC, >32 μg/mL; i.e., VRE), strains of enterococcus with reduced susceptibility to vancomycin (ERSV) were recovered from the other 22 subjects. Past use of vancomycin (P = .05) and tacrolimus therapy (P = .011) were independent risk factors for ERSV or VRE carriage. Enterococcal infections occurred with a similar frequency among enterococcal carriers and noncarriers; no infections with VRE or ERSV were reported. In conclusion, the prevalence of ERSV carriage and the rate of VRE colonization among mid-European children and adolescents with ESRF currently are moderate and low, respectively.
Participating members of the Mid-European Pediatric Peritoneal Dialysis Study Group: M. Zimmering (Berlin), U. Querfeld (Cologne, Germany), M. Böswald (Erlangen, Germany), K.E. Bonzel (Essen, Germany), D.E. Müller-Wiefel (Hamburg, Germany), O. Mehls and F. Schaefer (coordinator) (Heidelberg, Germany), J. Misselwitz (Jena, Germany), C. Greiner (Leipzig, Germany), G. Klaus (Marburg, Germany), B. Klare (Munich), E. Simkova (Prague), H.-J. Stolpe (Rostock, Germany), and M. Fischbach (Strasbourg, France)
Gesehen am 11.12.2020